Usamos todos, algunos y ninguno, al agrupar objetos - Garcia Bocanegra, Zadith (2019)
The work of professional sufficiency had the title: “We use all, some and none, when grouping objects”, whose development of the learning session it has been based on bibliographical references and other sources of consultation, as well as application of knowledge acquired during the academic years in my education and and agreement to the work done during the last years. Whose conclusions indicate what the process of solving problems implies that he student play, he manipulates objects, activates their own mental capacity, exercises their creativity, reflect and improve the thought process when applying and to adapt differents mathematical strategies in different contexts. The didactic processes allow to organize better the learning of the students, organizing their knowledge in an orderly manner, whose actions are managed and directed by the teacher inside a certain period of time, either inside or outside the classroom. The competence developed in the present session presents to "Solve problems of quantity", which consists of the student solving problems, which which consists in what the student solving problems or or raise new problems, that you sue to build and understand the notions of number, grouping and counting their operations and properties. Logical thinking is used when the student makes comparisons, explains the result of the analogies, induces properties from particular cases or examples in the resolution process of problems